The Analysis of Morphological Diversity and Polyphenols Content of Celosia cristata in M2 Population Induced by Ethyl Methane Sulphonate: Genetic diversity of mutated C. cristata - Waras Nurcholis; Syarifah Iis Aisyah; Yoshua Shandy Yudha; Dewi Sukma (Journal of Tropical Life Science, 2023)
Celosia cristata, an edible ornamental plant, is a potential floricultural commodity that needs further improvement to increase its agro-morphological characters and polyphenol content. Induced mutagenesis using ethyl methane sulphonate (EMS) is an effective tool to increase genetic diversity that has been applied in many plant species. This study aimed to assess the morphological diversity, polyphenol content, and antioxidant activities of C. cristata mutagenized by EMS in the M2 generation. A total of 230 M2 plants generated from the M1 generation were evaluated in this study and the polyphenols content and antioxidant activities analysis were conducted on fifteen selected M2 plants. Polyphenols content was analyzed using the Folin-Ciocalteu method and colorimetric method with slight modification, and the antioxidant activities investigated using 2,2’-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and ferric reducing antioxidant power (FRAP) assay with minor changes. There are six subpopulations with the highest diversity of quantitative characters in the M2 population in quantitative characters, i.e. C2-17-1.0%, C2-1-0.7%, C2-20-2.0%, C2-25-0.7%, C2-1-0.9%, and C2-1-0.7%. Changes in the shape and color of leaves, stems, and flowers of C. cristata were also observed in the M2 population. C2.1, C2.6, and C2.12. 2.1, C2.6, and C2.12 are potential plants derived from EMS mutagenesis with the highest polyphenol content and antioxidant capacity in the M2 population. In conclusion, induced mutation using EMS can enhance the agro-morphological diversity, polyphenols content along with the antioxidant activities of C. cristata, and demonstrate the successful mutation breeding program.